Dampak Penggunaan Gadget Terhadap Perkembangan Emosional Remaja - Miftahul Jannah; Mitsaqy Fitria Irdha; M. Malik Fajar Rambe; T. Chantiqa Salsabilla Az-Zahra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to investigate the impact of gadget use on the emotional development of adolescents. The research method used is Literature Review or literature review with descriptive analysis. Gadgets, as modern electronic media, have become an integral part of teenagers' daily lives. However, excessive use of gadgets can cause emotional changes, social isolation, and negative impacts on teenagers' academic performance. Gadget addiction can also affect mental health, with symptoms of anxiety and depression as possible impacts. Parents and families need to monitor and guide teenagers in using gadgets wisely to ensure a healthy balance between technology and real life. The research results show that excessive use of gadgets can cause emotional instability, social isolation, and impaired academic performance in adolescents. In conclusion, it is important to monitor teenagers' gadget use in order to maximize the positive benefits without compromising their emotional and social well-being.